Rancangan Penilaian Proses Dan Hasil Belajar Serta Berbagai Teknik Penilaian Dalam Pembelajaran Arab - Muhammad Zaidaan; Rafi Fitranur; Muhammad Refaldi; Teungku Afif Ahmad; Raswan Raswan (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2026)
Assessment is an essential component of the learning system that functions to measure students' competency achievement and serves as a basis for decision-making in the educational process. However, in the practice of Arabic language learning, assessment is still predominantly focused on measuring cognitive aspects through written tests, resulting in students' communicative competence, attitudes, and practical skills not being optimally assessed. This condition indicates a gap between the concept of authentic assessment recommended in the literature and its implementation in actual educational practice. This study aims to explain, analyze, and develop a framework for assessing both the learning process and learning outcomes by employing various relevant assessment techniques and integrating them into the preparation of Lesson Plans (RPP) and Teaching Modules (Modul Ajar). The study employed a descriptive qualitative approach through a literature review and the practice of designing instructional materials. The findings indicate that effective assessment should be authentic, continuous, and encompass the domains of attitudes, knowledge, and skills. The assessment techniques include observation, written tests, assignments, performance assessment, portfolios, self-assessment, and peer assessment. Furthermore, systematic assessment planning within Teaching Modules can improve the quality of instruction and assist teachers in comprehensively monitoring students' learning progress. The novelty of this study lies in its analytical framework that integrates various assessment techniques with the characteristics of Arabic language learning competencies, thereby providing recommendations for a more comprehensive, authentic, and practical assessment design for teachers. Therefore, a well-designed assessment system is expected to contribute to improving the overall quality of Arabic language learning